ETUDE DE L’INFLUENCE DU STRESS HYDRIQUE SUR DEUX LIGNEES DE NIEBE - Aziadekey, Mawuli; Atayi, Ayayi; Odah, Komi; Magamana, Abalo-Esso (European Scientific Journal, ESJ, 2014)
Drought is a major limiting factor for cowpea production in tropical countries. Therefore, the effects of water stress applied 8 and 16 days after flowering have been studied on two lines (V1 and V2) of cowpea for a double purpose use for seed and forage production. Parameters related to yield components, aerial and underground biomasses as well as total N and P contents of leaves and seeds were evaluated. The effects of 8 days of water stress after flowering were low on some yield components such as 100 seed weight and pods length for both lines. But, 16 days of water stress had greatly reduced all the agronomic and morphological traits, with a greater impact on V1 for the number of pods and total seed weight per plant. Consequently, this line was more sensitive for seed production under water stress condition because of a high sensibility index (1,20). However, this line could be better forage because of a higher production of aerial biomass. On the other hand, yield components such as the number of pods and total seed weight per plant were less reduced for V2. The index of sensibility for this line was 0,80 (S<1) indicating that it was less sensitive or tolerant to water stress for seed production. Both lines had a tendency to accumulate total N in their leaves with similar P content in their seeds. This study showed that line V2 had the best response under drought conditions, especially for seed production.